Draft Genome Sequences of Seven Streptococcus agalactiae Strains Isolated from Camelus dromedarius at the Horn of Africa - Rothen, Julian; Schindler, Tobias; Pothier, Joël F.; Younan, Mario; Certa, Ulrich; Daubenberger, Claudia A.; Pflüger, Valentin; Jores, Joerg (American Society for Microbiology, 2017)
We present draft whole-genome sequences of seven Streptococcus agalactiae strains isolated from Camelus dromedarius in Kenya and Somalia. These data are an extension to the group B Streptococcus (GBS) pangenome and might provide more insight into the underlying mechanisms of pathogenicity and antibiotic resistance of camel GBS.